Human rights under the rules of international law - Zaabal, Mohamed (Journal of Human Sciences, 2021)
The question of human rights is one of the subjects which has preoccupied and still preoccupies jurists of international law in general and of international human rights law in particular, because of the latter's close relationship with man and his environment, in order to ensure a life of dignity for this human being, which makes it necessary to remove any confusion as to the conceptual framework of these rights, in particular by highlighting their particularities, without neglecting the different classifications of those rights, as well as the sources from which these rights derive their foundations, in order to simplify more profoundly due to the repercussions of this in the field of international jurisprudence, which will have a significant impact in the future by raising the field of international protection of these rights.